From Spirituality to Social Empowerment: The Role of Islamic Dakwah and Sufism in Contemporary Community Development in Southeast Asia - Uyuni, Badrah; Adnan, Mohammad; Muhibudin (Southeast Asia Development Research, 2025)
This conceptual study develops the Spiritual-Social Dakwah (SSD) Framework, a normative-analytical paradigm that reorients Islamic dakwah and community development in contemporary Southeast Asia. Employing a qualitative-conceptual design grounded in interpretive analysis of classical Islamic scholarship and a thematic review of recent literature, the SSD Framework integratively synthesizes Sufistic spirituality, fiqh al-dakwah (jurisprudence of preaching), maqāṣid al-sharī‘ah (objectives of Islamic law), and wasatiyyah (moderation) into a holistic model of faith-based empowerment. It bridges the persistent divide between personal piety and socio-economic transformation through three operational domains: tazkiyah (spiritual-ethical formation), ta‘āwun (collaborative social engagement), and taṭāwwur (institutional-digital innovation). While conceptually rooted in the Indonesian context, the framework engages comparative insights from across Southeast Asia and acknowledges implementation challenges, particularly the risk of instrumentalizing spirituality within development agendas. The SSD model aligns Islamic ethical values with the Sustainable Development Goals (SDGs), offering a coherent theoretical foundation for transforming mosques and majelis taklim (Qur’anic study groups) into hubs of inclusive social empowerment. Its principal contribution lies in renewing dakwah epistemology from predominantly ritual discourse toward socially embedded and institutionally adaptive praxis while outlining a strategic agenda for future empirical validation, cross-regional comparison, and the development of context-sensitive impact indicators for faith-based community development.